2015
DOI: 10.18632/oncotarget.4740
|View full text |Cite
|
Sign up to set email alerts
|

miR-25 promotes hepatocellular carcinoma cell growth, migration and invasion by inhibiting RhoGDI1

Abstract: MicroRNA (miRNA)-25 is a small non-coding RNA that has been implicated in the tumorigenesis of many cancers, but little is known on the role of miR-25 in HCC metastasis. We hereby found that miR-25 was significantly upregulated in clinical HCC tissues compared with normal liver tissues. We also revealed that miR-25 dramatically stimulates HCC cell growth and activates the epithelial-mesenchymal transition (EMT). MiR-25 is activated by the WNT/β-catenin signaling pathway, and exerts its pro-metastatic function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 31 publications
(36 reference statements)
2
52
0
Order By: Relevance
“…They reported that miR‐25 induced migration and invasion in these HCC cell lines in vitro and tumor growth and metastasis in vivo , supporting the important role of miR‐25 in liver cancer. The authors claimed that the effect of miR‐25 overexpression was dependent on direct targeting of RhoGDI1, which in turn promoted epithelial‐mesenchymal transition . In the present study, we found that RhoGDI1 transcript levels were significantly decreased in HepG2 but not in the HCC HBV‐positive cell line SNU398 (Supporting Information Table S4).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…They reported that miR‐25 induced migration and invasion in these HCC cell lines in vitro and tumor growth and metastasis in vivo , supporting the important role of miR‐25 in liver cancer. The authors claimed that the effect of miR‐25 overexpression was dependent on direct targeting of RhoGDI1, which in turn promoted epithelial‐mesenchymal transition . In the present study, we found that RhoGDI1 transcript levels were significantly decreased in HepG2 but not in the HCC HBV‐positive cell line SNU398 (Supporting Information Table S4).…”
Section: Discussionsupporting
confidence: 54%
“…In our study, we focused on the potential function of these deregulated miRNAs and showed that overexpression of miR‐25 promoted cell proliferation both in monolayer and in anchorage‐independent conditions. In a recent study, Wan and collaborators also showed that miR‐25 induced cell proliferation in vitro in the Hepatitis B virus (HBV) negative HCC cell lines HepG2 and Huh7 . They reported that miR‐25 induced migration and invasion in these HCC cell lines in vitro and tumor growth and metastasis in vivo , supporting the important role of miR‐25 in liver cancer.…”
Section: Discussionmentioning
confidence: 85%
“…Unique patterns of miRNA expression have been established as a potential marker for sub-classification, diagnosis, prognosis, and therapeutic targets in HCC. Reports show that various miRNAs involve in HCC oxidative stress, cell proliferation, cell-cycle, and progression [6][7][8][9][10]. In this study, we elucidated the post-transcriptional inhibition of ZEB2 under the regulation of miR-211-5p in HCC cells.…”
Section: Discussionmentioning
confidence: 77%
“…It is reported that up-regulated miRNAs and down-regulated miRNAs involve in HCC progression and play important roles in HCC [2][3][4][5]. Reports show that miR-17-92 cluster, miR-1180, miR-107, and miR-25 are consistently up-regulated in primary HCC tissues [6][7][8][9]. MiR-192, miR-122, miR-34a, and miR-149 are commonly down-regulated in HCC [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs impact the dynamic balance between anti-tumor genes and oncogenes by regulating target genes, then influenced cancer growth [10]. miR-25 has been shown to be related with tumor carcinogenesis, including hepatocellular carcinoma [11], breast cancer [12], cholangiocarcinoma [13], and ovarian cancer [14]. However, the function of miR-25 in melanoma invasion and metastasis remains unclear.…”
Section: Discussionmentioning
confidence: 99%